IMPLEMENTASI PERATURAN KEPOLISIAN NOMOR 6 TAHUN 2018 TERHADAP TATA CARA PENGAJUAN PERCERAIAN BAGI ANGGOTA KEPOLISIAN DI POLRES SORONG SELATAN - Isabela Dita Nintiyas B; Weron Murary; Raymond R Morintoh (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: The purpose of this research is that divorce is the process of ending a marital relationship between a man and a woman as husband and wife, carried out in court. However, if police members frequently experience conflicts in their married life that threaten the integrity of their household, it must be immediately reported to Ankum (the superior authorized to take disciplinary action) so that corrective measures can be taken. For police members, the regulation regarding the authorized official who can grant a divorce permit according to Police Regulation Number 6 of 2018 at the Police Resort level is the Chief of Police Resort (Kapolres) for ranks of Brigadier and Civil Servants in grade II and below in their area. A wife or husband who is not a member of the police still has to inform the superior of their spouse who is a police officer about any divorce plans and family issues. This is because they married a police officer and became part of the police family, so they are automatically bound by police regulations. This research is an empirical legal study. Empirical legal research is commonly referred to as field research, which is research oriented toward collecting empirical data in the field. Thus, the primary data in this study is data taken from the first source in the form of interviews with respondents considered appropriate for data collection. As additional material, there are also written sources, which can be divided into: books, scientific journals, archival sources, personal documents, undergraduate or thesis papers, journals, and official documents. In this study, the author analyzes the implementation of Police Regulation Number 6 of 2018 regarding the Procedures for Filing Divorce for Police Members at the South Sorong Police. From the research results, it was found that filing for divorce by police members requires attention, especially if the divorce petition is filed by a police member who has the status of a civil servant (ASN). In that case, they must obtain permission from their superior before filing for divorce. After getting the permission, the police member can submit a divorce petition according to the applicable legal procedures. The police are advised to complete the required documents, and once complete, a mediation process will be conducted at least 3 times. If no agreement is reached, a Divorce Permit Letter will be issued, signed by the Police Chief, as one of the administrative requirements for civil servants in the police to register the divorce petition in court. Police officers have to submit an official request for divorce permission to the authorized officer, like the Kasatker. Once the request is accepted, the authorized officer will provide guidance to help reconcile the husband and wife. If mediation doesn’t work, the authorized officer will take written statements and analyze them to give a recommendation to the authorized officer. After all the processes are completed, the authorized officer can issue a divorce permission letter so the divorce proceedings can continue in court.Keywords: Divorce Filing, South Sorong Police, Police Officer